(untitled) (Fiep Bulletin - online, 2014)
The subject of study is Public Politics of carried through Sports and Leisure in the city of Petrópolis -Rio de Janeiro, With objective of beginning a process of access enlargement to the Leisure, Sports and activities in the schools, and free time, they grew several projects and sporting programs returned to the service of the less favored population. Like this, it was drawn the beginning of a new time of expressive modifications of the picture until then predominant. The verification of absence of evaluations of the programs of Sports and Leisure developed in the municipal district of Petrópolis, it indicates the need and the development of methodologies that offer as resource the evaluation of the efficiency, of the effectiveness and of the effectiveness of the politics, as for the possibilities of verification of cultural modifications (as for the form of enjoying of the material goods, leisure equipments, facilities and entertainments), as for the perceptions of having involved in the improvement of the quality of life and access conditions and health. The initiate research in 2005 intends to verify the hypothesis of these projects generated modifications that can verify the assertiveness of the investment in programs of Leisure and Sport. Through investigations driven through questionnaires and rising of information declared by the municipal administration we produced an analysis picture capable to refer on the future interventions. The qualitative and descriptive methodology, was used of instrument applied in one hundred children, as indications of Tubino (2006) The results: we supposed that the current situation of the picture of politics developed by the current administration in the period, 2001 until the present are superior to the previous picture, in an universe of a hundred children, in 60 thousand students in the 67 municipal schools. Real improvements, (qualitative), for instance, in the school acting of 60% of the students.